Structural and Meaning Analysis of Pantun Melayu in Malay Arabic Script Texts - Warni Warni; Irma Suryani; Rengki Afria; Ahyatun Maghfiroh (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2022)
Abstract: The purpose of this study is to describe the results of the analysis of the structure and meaning of the Malay pantun. Pantun is a culture that develops in Malay land and its presence continues to be preserved and maintained until today. This research is an elaboration of the structure and meaning of the Malay pantun with the Malay Arabic script, which is then transcribed in order to understand the meaning contained in it. This study uses a qualitative descriptive analysis method, the data source used is the text of the Malay pantun with Malay Arabic script, the data collection technique is carried out by document study, the method of presenting the results of data analysis is an analysis of the structure and meaning of the Malay pantun by identifying and describing it. The structure that builds the Malay pantun in each stanza consists of four lines with words ranging from three to five words and syllables ranging from eight to eleven syllables. The rhymes that are owned by the a-b-a-b rhyme are found in three types of rhymes, including perfect rhymes, imperfect rhymes, and perfect double ending rhymes. The meaning found is in the form of intertainment and advice or teachings that contain moral messages in the form of virtues that are expected to be taught and continue to be preserved as good morals for the Malay community. Keyword: Structure, Mean, Pantun, Script, Malay.